2016
DOI: 10.2147/copd.s115238
|View full text |Cite
|
Sign up to set email alerts
|

Management of COPD, equal treatment across age, gender, and social situation? A register study

Abstract: Chronic obstructive pulmonary disease (COPD) is a progressive chronic disease where treatment decisions should be based on disease severity and also should be equally distributed across age, gender, and social situation. The aim of this study was to determine to what extent patients with COPD are offered evidence-based interventions and how the interventions are distributed across demographic and clinical factors in the sample. Baseline registrations of demographic, disease-related, and management-related vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 23 publications
4
22
1
2
Order By: Relevance
“…Our findings of ethnic differences are in keeping with a US study showing that Afro-American patients were less likely to receive recommended care during a hospitalization for acute COPD exacerbation than Caucasian and Hispanic patients, and that this could be explained by Afro-American patients generally attending poor performance hospitals [9]. In contrast, our findings of a lower chance of receiving optimal care among patients living alone, a recent Swedish study indicated that patients living with someone were less likely to have contact with a physiotherapist and dietician and participate in smoking cessation programs [8]. This opposing finding could be due to differences in study populations, the Swedish study being dominated by relatively younger and less severely ill study patients followed in primary care where patients cohabiting may to larger extend depend on their partners for non-pharmacologic lifestyle interventions.…”
Section: Main Findingscontrasting
confidence: 58%
See 1 more Smart Citation
“…Our findings of ethnic differences are in keeping with a US study showing that Afro-American patients were less likely to receive recommended care during a hospitalization for acute COPD exacerbation than Caucasian and Hispanic patients, and that this could be explained by Afro-American patients generally attending poor performance hospitals [9]. In contrast, our findings of a lower chance of receiving optimal care among patients living alone, a recent Swedish study indicated that patients living with someone were less likely to have contact with a physiotherapist and dietician and participate in smoking cessation programs [8]. This opposing finding could be due to differences in study populations, the Swedish study being dominated by relatively younger and less severely ill study patients followed in primary care where patients cohabiting may to larger extend depend on their partners for non-pharmacologic lifestyle interventions.…”
Section: Main Findingscontrasting
confidence: 58%
“…To our knowledge, the association between SES and quality of outpatient care for COPD patients is largely unexamined. A recent study using the Swedish National Airway Register indicated that patients living with someone were less likely to have contact with a physiotherapist and dietician and participate in smoking cessation programs [8]. However, the study population predominantly included patients from primary care in the earlier stages of disease.…”
Section: Introductionmentioning
confidence: 99%
“…The results were equal to another survey conducted in Sweden, which showed that drug treatment depended on disease severity. 36 More than 70% of the patients were satisfied with COPD drugs. Approximately 80% of the patients did not know the side effects of anticholinergic drugs, β-adrenergic agonists, ICSs, ICS/long-acting β2-agonist, and theophylline.…”
Section: Discussionmentioning
confidence: 99%
“…At that time, the variables in SNAR were modified to harmonize with these recommendations, which presents a unique opportunity to use data from SNAR to evaluate the effect of this national effort. Several papers presenting COPD data from SNAR have been published [19][20][21][22]; however, a comprehensive presentation of SNAR across the spectrum of obstructive lung disease has not yet been undertaken. Accordingly, this paper aims to describe the development and design of SNAR, and to study the 2019 data to evaluate its potential utility related to improvement of quality of care.…”
Section: The Swedish National Airway Registermentioning
confidence: 99%